Uncovering key targets of success for immunotherapy in pancreatic cancer. (2nd November 2021) - Pretta, Andrea; Lai, Eleonora; Persano, Mara; Donisi, Clelia; Pinna, Giovanna; Cimbro, Erika; Parrino, Alissa; Spanu, Dario; Mariani, Stefano; Liscia, Nicole; Dubois, Marco; Migliari, Marco; et al.
ABSTRACT: Introduction: Despite available treatment options, pancreatic ductal adenocarcinoma (PDAC) is frequently lethal. Recent immunotherapy strategies have failed to yield any notable impact. Therefore, research is focussed on unearthing new drug targets and therapeutic strategies to tackle this malignancy and attain more positive outcomes for patients. Areas covered: In this perspective article, we evaluate the main resistance mechanisms to immune checkpoint inhibitors (ICIs) and the approaches to circumvent them. We also offer an assessment of concluded and ongoing trials of PDAC immunotherapy. Literature research was performed on Pubmed accessible through keywords such as: 'pancreatic ductal adenocarcinoma, ' 'immunotherapy, ' 'immunotherapy resistance, ' 'immune escape, ' 'biomarkers.' Papers published between 2000 and 2021 were selected. Expert opinion: The tumor microenvironment is a critical variable of treatment resistance because of its role as a physical barrier and inhibitory immune signaling. Promising therapeutic strategies appear to be a combination of immunotherapeutics with other targeted treatments. Going forward, predictive biomarkers are required to improve patient selection. Biomarker-driven trials could enhance approaches for assessing the role of immunotherapy in PDAC.